The Environmental Litigation Bond: An Illegal and Shortsighted Limitation on Environmental Litigation in Utah (Utah Environmental Law Review; Vol 33 No 1 (2013), 2014)
Utah Governor Gary R. Herbert signed House Bill 399, the Environmental Litigation Bond, into law on March 21, 2011. The Environmental Litigation Bond requires parties seeking a preliminary injunction or administrative stay related to state environmental permitting decisions to post a bond covering the costs that are likely to be incurred by the defendant due to project delays resulting from litigation.